Respiratory variability of inferior vena cava at different mechanical ventilator settings - (:unkn) unknown (W B SAUNDERS CO-ELSEVIER INC, 2021)
Background: Assessment of the respiratory changes of the inferior vena cava (IVC) diameter have been investigated as a reliable tool to estimate the volume status in mechanically ventilated and spontaneously breathing patients. Our purpose was to compare the echocardiographic measurements the IVC diameter, stroke volume and cardiac output in different positive pressure ventilation parameters. Methods: This prospective clinical study with crossover design was conducted in the Intensive Care Unit (ICU). Twenty-five sedated, paralyzed, intubated, and mechanically ventilated patients with volume control mode (CMV) in the ICU due to respiratory failure were included in the study. Positive End-Expiratory Pressure (PEEP) and Tidal Volume (TV) were changed in each patient consecutively (Group A: TV 6 ml/kg, PEEP 5 cmH20, B: TV 6, PEEP 8, C: TV 8, PEEP 5, D: TV 8, PEEP 8) and the changes in vital parameters, central venous pressure (CVP) and ultrasonographic changes in IVC and cardiac parameters were measured. All measures were compared between groups by robust repeated measures ANOVA with trimmed mean. Results: The respiratory changes of the IVC diameter and echocardiographic parameters showed no significant difference in separate mechanical ventilator settings. Significant difference was found in peak and plateau pressure values among groups (p < 0.05). Conclusion: The results of our study suggest that IVC related parameters are not affected with different ventilatory settings. Further studies are needed to confirm the reliability of these parameters as a predictor of fluid assessment. (c) 2021 Elsevier Inc. All rights reserved.
Keywords: PEEP; Tidal volume; Inferior vena cava distensibility; Mechanical ventilation; PREDICTING FLUID RESPONSIVENESS; END-EXPIRATORY PRESSURE; SONOGRAPHIC MEASUREMENT; DIAMETER; APPROPRIATE; ULTRASOUND; SOCIETY; SHOCK